Innovative approaches to financial flow management in global value chains - Sobko, Yurii (Актуальні питання економічних наук, 2025)
In the context of growing international interdependence, the efficiency of financial resource management is determined by the ability of systems to ensure transparency, flexibility, and transaction speed. It requires the implementation of innovative approaches that integrate financial management, digital technologies, and data analytics. The purpose of the study is to provide a theoretical generalization and practical justification of mechanisms for innovative financial flow management under conditions of economic digital transformation. Methods. The research applies a systemic and structural-functional approach, comparative analysis of international digital indices, and logical generalization, which made it possible to identify the relationship between a country’s digital readiness and the implementation of innovations in financial management. Results. The study found that digital readiness of the economy is a key prerequisite for innovation in the financial sphere. At the same time, its asymmetry – between high human capital and a weak level of business digitalization –creates the need for new approaches to financial flow coordination. Based on a comparative analysis of the Network Readiness Index (NRI), DiGiX, and Cisco DRI, it was found that Ukraine possesses favorable human and technological conditions for FinTech development but remains constrained by institutional barriers and insufficient investment in digital infrastructure. The study develops an analytical approach to managing financial flows within global value chains (GVC), grounded in the integration of innovative technologies – blockchain, artificial intelligence, smart contracts, FinTech platforms, and cloud systems. The proposed framework of innovative solutions reflects their functional purpose and their impact on the efficiency of financial management in GVCs. The application of these technologies enhances financial monitoring accuracy, reduces transaction costs, accelerates capital circulation, and strengthens trust among participants in the global economic network. The practical significance of the results lies in the use of the proposed approach to improve financial flow management and to support the development of digital strategies for sustainable economic growth.